Gradient glass-like ceramic structures and bottom-up preparation methods

By using negatively charged β-silsesquioxane and organic functional silane compositions, a SiO2-rich structure with gradient properties is formed, solving the challenge of manufacturing high-density silica thin films at low temperatures, and achieving microscopic at low temperatures Contact printing and direct writing overcomes the chemical interaction and wetting problems of traditional technologies, and improves the flexibility and accuracy of manufacturing complex devices.

CN115380013BActive Publication Date: 2024-12-27GELEST INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180027723.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-04-06
Filing Date
2021-04-01
Publication Date
2024-12-27
Estimated Expiration
2041-04-01

AI Technical Summary

Technical Problem

The prior art is difficult to manufacture high-density silica thin films at low temperatures, and traditional grinding and etching techniques have chemical interactions and wetting problems, limiting the complex structure manufacturing of microelectronic devices.

Method used

Using silsesquioxane and organofunctional silane compositions with negatively charged beta substituents, a SiO2-rich structure with gradient properties is formed by coating and heating or ultraviolet irradiation, so as to achieve micro-contact printing and direct writing at low temperatures. Overcome the limitations of traditional methods.

Benefits of technology

It realizes the manufacture of glass-like ceramic films with spatial gradient characteristics at low temperatures, which are non-permeable and fluid-resistant, suitable for the manufacturing of complex devices, and adjusts surface characteristics through surface patterning technology, improving manufacturing flexibility and accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115380013B_ABST
    Figure CN115380013B_ABST
Patent Text Reader

Abstract

Glassy ceramic films with organic or physically functional structures having a thickness in the range of 15 to 500 nanometers and a bottom-up method for their production are described. The SiO2-rich structures with gradient properties are formed from silsesquioxanes with electronegative β-substituents and at least one organofunctional silane or at least one metal alkoxide.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. Provisional Patent Application No. 63,005,506, filed on April 6, 2020, the disclosure of which is incorporated herein by reference. Background of the Invention

[0004] Silicon dioxide (SiO2) films and substrates are essential structural components of diagnostic, optical, and microelectronic devices in widespread use today. These SiO2-containing films are typically made using grinding and etching techniques or using well-known silanes (e.g., SiH4), silane esters (e.g., tetraethoxysilane (TEOS)), or silsesquioxanes (e.g., hydrogen silsesquioxane resins, as described in U.S. Pat. No. 5,290,354 to Haluska and U.S. Pat. No. 5,320,863 to Ballance et al.). The goal of all of these techniques is to create a unified mechanical, optical, or electronic structure that is stable and does not interact or affect the chemical or wetting processes of the device. Essentially, the devices require that the glass or glass-like structure be an inert structural component.

[0005] Sommer et al., "Organosilicon Compounds V. β-Eliminations Involving Silicon", Journal of the American Chemical Society, Vol. 68, pp. 1083-1085 (1946), summarizes the chemical reaction studies of β-chloroethyltrichlorosilane and β-chloro-n-propyltrichlorosilane, including the synthesis of β-chloroethylsilane. 1.5 The β-chloroethylsilyl polymers react with dilute base to give ethylene and Si(OH)4. No end use of these compounds has been suggested. Summary of the invention

[0006] According to one embodiment, the present invention relates to a SiO2-rich structure having a gradient nature, wherein the structure is formed from a silsesquioxane having electronegative β-substituents and at least one organofunctional silane.

[0007] Another aspect of the present invention relates to a SiO2-rich structure having a gradient concentration of at least one metal oxide selected from the group consisting of germanium, tantalum, titanium, zirconium and hafnium, wherein the structure is formed from the corresponding metal alkoxide and a silsesquioxane having an electronegative β-substituent.

[0008] Yet another aspect of the present invention relates to a method for forming a SiO2-rich structure having gradient properties, the method comprising preparing a coating composition comprising a silsesquioxane having electronegative β-substituents, at least one organofunctional silane, and optionally a solvent, applying the mixture to a substrate, and heating and / or ultraviolet irradiating the coated substrate.

[0009] Another aspect of the present invention relates to a method for forming a SiO2-rich structure with gradient properties, the method comprising preparing a coating composition comprising a silsesquioxane having electronegative β-substituents, at least one metal alkoxide, and optionally a solvent, applying the mixture to a substrate, and heating and / or UV irradiating the coated substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 is a diagram showing the synthesis of a product of one example of the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0013] Some aspects of the present invention relate to glassy thin ceramic films with organic or physically functional structures with thicknesses ranging from 15 to 500 nanometers and bottom-up preparation methods thereof. The physicochemical properties of these structures have spatial gradient characteristics, i.e., properties that vary over a certain length of space. The structures and methods described herein overcome previous challenges in the manufacture of high-density silicon dioxide at low temperatures, where the gradient is caused by diffusion, etching, or by changes in energy intensity of thermal, photolytic or other energy methods that convert ceramic precursors to ceramics. The technology described herein allows microcontact printing and direct writing of silicon dioxide (SiO2)-based ceramics at low temperatures (<250°C) with the ability to adjust the surface and volume. Transparent glassy ceramic structures consistent with bottom-up processing can be deposited by spin coating, direct writing or microcontact printing techniques. The coating is non-permeable and can resist a variety of fluids, from aqueous systems with extreme pH values ​​to solvent-based systems, and the channels will not deform or fail. The method also allows local changes to the surface through various surface patterning techniques. Compared with etching and grinding processes, this bottom-up approach facilitates complex device manufacturing.

[0014] As described in more detail below, according to one embodiment of the present invention, a method for producing a SiO2-rich material or structure having gradient properties includes combining one or more organofunctional silanes (e.g., organofunctional alkoxysilanes) with an electronegative β-substituted silsesquioxane-based polymer.

[0015] The beta substituent of the silsesquioxane polymer is located at the beta carbon of the alkyl group, sometimes referred to as the 2-carbon position, relative to the carbon-silicon bond. The beta-substituted alkyl group is bonded to silicon at the alpha- or 1-carbon position.

[0016] U.S. Pat. Nos. 5,853,808 and 6,770,726, the entire contents of which are incorporated herein by reference, as well as publications J. Sol-Gel Sci Tech, 8, 465 (1997) and J. Mater. Res. 14 (3), 990 (1999), show that organosiliconesquioxanes having electron-withdrawing substituents in the β position are converted to SiO2 via a chemical route involving the elimination of ethylene and then hydrolytic condensation, as shown in Scheme 1 below. The conversion can be initiated by heat or ultraviolet exposure. These materials will be referred to herein as "silsesquioxane polymers".

[0017]

[0018] Silsesquioxane polymers may also include partial substitution of the polymer backbone, which is substituted by negatively charged groups directly attached to the silicon atoms of the backbone, rather than being attached through CH2CH2, as in acetoxyethyl silsesquioxane-acetoxy silsesquioxane copolymers. Silsesquioxane polymers may also include other copolymers in which hydrolyzable alkoxy groups are present, such as acetoxyethyl silsesquioxane-ethoxy silsesquioxane copolymers and acetoxyethyl silsesquioxane-methoxypropoxy silsesquioxane copolymers, but preferably the hydrolyzable substituents account for less than 20% of the copolymer. Alkoxy silsesquioxane or substituted alkoxy silsesquioxane copolymers may be easily formed by heating or storing the silsesquioxane homopolymer in a solution containing an alcohol, such as ethanol, methoxyethanol or methoxypropanol. In a preferred embodiment, 2-acetoxyethyl is a preferred primary comonomer, and alkyl ether substituted alkoxy is a preferred substituent for the secondary comonomer.

[0019] Upon subsequent heating of the β-substituted organosilsesquioxane polymer under relatively moderate temperature conditions (e.g., above about 150° C.) or by exposure to ultraviolet radiation, the unstable β-substituted alkyl groups appear to be volatilized and substantially eliminated, and the silsesquioxane polymer is converted to a SiO2-rich ceramic material suitable for preparing thin films or layers on electronic substrates.

[0020] An exemplary reaction for forming a SiO2-rich structure having gradient properties as described herein is shown in Scheme 2.

[0021]

[0022] Upon heating, the silsesquioxane polymer (Structure 1 in Scheme 2) with residual hydroxyl groups condenses with an organofunctional alkoxysilane to form an intermediate silsesquioxane of the present invention (Structure 2 in Scheme 2). Such organofunctional silane-modified silsesquioxane polymers of the present invention will be referred to herein as "silsesquioxane deposition polymers". The silsesquioxane deposition polymer is formed by reacting the hydroxyl groups (silanols) of the silsesquioxane polymer with an organofunctional alkoxysilane or metal alkoxide. Heating simultaneously drives a condensation reaction in which the hydroxyl groups on the silsesquioxane replace the alkoxy groups, releasing an alcohol, and a rearrangement reaction in which the acetoxy groups migrate to silicon with the loss of ethylene. In a second moisture-driven step, the acetoxy groups are hydrolyzed and condensation of a ceramic resin occurs. Not shown, but understood, the second stage hydrolysis-condensation reaction requires the formation of silanols, which can react with any remaining alkoxy groups of the alkoxysilane. In the case where the silsesquioxane-based polymer comprises a copolymer in which hydrolyzable groups are present, such as in acetoxyethylsilsesquioxane-methoxypropoxysilsesquioxane copolymers, deposition is preferably performed in a high humidity environment to initiate conversion of the hydrolyzable groups to silanols.

[0023] The silsesquioxane deposition polymers suitable for forming the SiO2-rich structures of the present invention are polymer reaction products obtained from β-substituted alkyl silsesquioxane-based polymers, which are derived by adding an organofunctional silane prior to or simultaneously with conversion to the SiO2-rich material. The organosilane has the general formula R n SiX (4-n) , wherein n is 1 or 2; X is a hydrolyzable group selected from chlorine, bromine, fluorine and iodine, or an alkoxy group preferably selected from the group consisting of methoxy, ethoxy and propoxy substituents.

[0024] Very preferably, the β-substituted organosilicon polymer is a polymerization reaction product obtained by hydrolysis and polycondensation of an organosilane containing a β-substituted ethyl group; preferably the organosilane includes, but is not limited to, β-acetoxyethyltrimethoxysilane CH3COOCH2CH2Si(OCH3)3 and acetoxyethyltrichlorosilane CH3COOCH2CH2SiCl3, which contains hydroxyl groups (silanol groups) bonded to silicon, as shown in the first structure of Scheme 2.

[0025] The silsesquioxane polymer is preferably a polymer reaction product obtained by homopolymerization of an organosilane. In another embodiment, the β-substituted organosilsesquioxane polymer may be a polymer reaction product obtained by copolymerization of the organosilane with an alkoxysilane (e.g., tetraalkoxysilane or an organic substituted alkoxysilane). The alkoxysilane is preferably selected from the group consisting of tetraalkoxysilanes such as tetraethoxysilane (TEOS), tetramethoxysilane (TMOS) and methoxytriethoxysilane, triethoxychlorosilane and organic substituted alkoxysilanes such as bis(trimethoxysilyl)ethane, methyltriethoxysilane, vinyltriethoxysilane, pentafluorophenyltriethoxysilane, tridecafluorooctyl-1H, 2H, 2H-octyltriethoxysilane and phenyltrimethoxysilane.

[0026] The silsesquioxane polymer obtainable by the hydrolysis and polycondensation of the β-substituted organosilane must contain free silanol groups (Si-OH), i.e., unreacted or uncondensed silanol groups. Preferably, the silsesquioxane polymer contains at least about 5 silanol groups per 100 silicon atoms in the polymerized reaction product and at most about 75 silanol groups per 100 silicon atoms. More preferably, the silsesquioxane polymer contains from about 20 to about 50 silanol groups per 100 silicon atoms in the polymerized reaction product.

[0027] Preferably, the free silanol content of the polymer reaction product is high and this content can be maintained by neutralizing the reaction mixture and recovering the polymer reaction product and maintaining the polymer in the form of a solution in a polar solvent.

[0028] Silsesquioxane polymers are obtained by hydrolysis and condensation of β-substituted organosilanes, in homopolymerization of organosilane monomers or copolymerization as described above. The hydrolysis and condensation polymerization reactions are exothermic and can be controlled by factors that are generally important in such hydrolysis and condensation reactions, and some of these factors are described below.

[0029] Hydrolysis and polycondensation can be carried out in conventional equipment by adding the organosilane monomer (or two monomers in the case of copolymerization) to an aqueous medium. The aqueous medium can be simply water or an aqueous alcohol. The monomer can be added pure or can be first dissolved in a solvent, such as dichloromethane. The monomer is preferably added to the aqueous medium at a measured rate (e.g., slowly) to obtain more precise control of the hydrolysis and condensation.

[0030] Additional control over the hydrolysis and polycondensation reactions can be obtained by adjusting the temperature of the aqueous reaction medium by maintaining the reaction temperature in the range of about 0° C. to about 50° C. Preferably, the temperature of the aqueous reaction medium is maintained at a temperature near (but above) the freezing point of the aqueous medium, preferably about 0° C. to about 5° C.

[0031] At the preferred reaction temperatures, the hydrolysis and condensation reactions occur more slowly. This allows, for example, the level of silanol content in the polymeric reaction product to be adjusted with greater control and precision. The preferred hydrolyzable substituents are alkoxy groups, since hydrolysis is less exothermic even under acid catalysis and generally produces silsesquioxane polymers having a higher hydroxyl content.

[0032] The polymerization product, i.e., the β-substituted organosilsesquioxane polymer, can be recovered from the aqueous reaction medium using conventional techniques, such as solvent extraction (with an organic solvent that dissolves the polymerization product but is immiscible with the aqueous reaction medium), salting out of the polymerization product, etc. The polymerization product can then be recovered as a substantially pure material (i.e., polymer) in solid form by filtering or evaporating the extraction solvent used.

[0033] Silsesquioxane Deposition Polymer

[0034] Preferred soluble and liquid homopolymer and copolymer silsesquioxanes having substitution in the beta position of the organic substituent include halogens (such as 2-chloroethyl silsesquioxane and 2-bromoethyl silsesquioxane), ethers (such as 2-methoxyethyl silsesquioxane), and carboxylates (such as 2-acetoxyethyl silsesquioxane). These materials can be considered as a base polymer of a continuous structure, which is then modified by varying one or more of the coreacting components to form a gradient upon ceramic conversion.

[0035] When no alkoxysilane or metal oxide is added with the silsesquioxane during synthesis, the base polymer becomes the deposition polymer. In the examples described below, at the exact midpoint, there is an unmodified silsesquioxane polymer; at all other points during the synthesis, it is modified by an alkoxysilane or metal oxide co-reactive component or additive.

[0036] Because inorganic acid byproducts are likely to react with organic substituents, acetoxy groups are preferred in the β position because acetic acid is a byproduct. Preferred organosilsesquioxanes of the present invention are 2-acetoxyethyl silsesquioxanes, and more preferred are organosilsesquioxanes having hydroxyl substitutions on the polymer backbone, known as silanols. An exemplary preferred silsesquioxane, acetoxy silsesquioxane, has formula (I), where R is 2-acetoxyethyl (CH3COOCH2CH2-).

[0037]

[0038] Organofunctional silane

[0039] Suitable organofunctional silanes for forming structures rich in SiO2 as described herein are preferably organofunctional alkoxysilanes. When preparing structures rich in SiO2, it is within the scope of the present invention to include one, two or more of these silanes. Suitable alkoxysilanes are typically trialkoxysilanes, but dialkoxysilanes may also be used, wherein the alkoxy group is a methoxy or ethoxy group (which results in volatile byproducts with low quality), such as those containing alkyl substituents (dialkyldialkoxysilanes, alkyltrialkoxysilanes). Preferred alkoxy groups include methoxy and ethoxy groups. Although it is within the scope of the present invention to use silanes with higher alkoxy groups such as propoxy and isopropoxy, the resulting film is more susceptible to cracking. Suitable alkyl groups include alkyl groups with one carbon atom (methyl) to more than twenty carbon atoms. Alkyl groups are substituted, such as methoxy (polyethyleneoxy) groups, and also fall within the scope of the present invention. It is also within the scope of the present invention to use silanes containing aromatic substituents, such as, but not limited to, phenyltrimethoxysilane. Preferred alkoxysilanes include isobutyltriethoxysilane and methoxy(polyethyleneoxy)propyltrimethoxysilane, as shown below.

[0040]

[0041] Metal alkoxide

[0042] It is also within the scope of the present invention to replace the alkoxysilane with one or more metal alkoxides, such as, but not limited to, germanium isopropoxide to produce a germanium oxide gradient, tantalum ethoxide to produce a tantalum oxide gradient, titanium n-butoxide to produce a titanium oxide gradient, zirconium n-propoxide to produce a zirconium oxide gradient, and hafnium n-butoxide to produce a hafnium oxide gradient. The use of these metal oxides will produce SiO2-rich structures that combine these elements and, among other properties, will produce a refractive index gradient that can be used in optical devices such as lenses, waveguides, and optical fibers. An exemplary reaction scheme is shown in Scheme 3 below.

[0043]

[0044] SiO2-rich structures with gradient properties

[0045] The term SiO2-rich is used herein to describe a structure in which a plurality of silicon atoms are each bonded to four oxygen atoms and no more than about 50% of the silicon atoms are bonded to carbon atoms.

[0046] The SiO2-rich structure is preferably in the form of a thin film having a thickness of about 15 nm to about 500 nm. It is also within the scope of the present invention to prepare thicker films (e.g., those having a thickness of up to 1500 nanometers), but such films are more likely to have stress cracks or defects.

[0047] Non-planar active structures that can be written into lines can be formed by combining the above-mentioned silsesquioxane-based polymers with metal alkoxides (including organofunctional silanes, such as the above-mentioned organofunctional alkoxysilanes) and metal alkoxides (such as germanium ethoxide) before undergoing the elimination-condensation reaction. Organic functional groups can be introduced during the distribution and / or writing process to change the concentration and produce gradients. In the spin-coating deposition method, the deposited polymer can produce a refractive index gradient by increasing the concentration of germanium alkoxide. Therefore, the outer part of the film will have a relatively low refractive index, while the central part will have a higher refractive index. The ceramic structure, although planar, behaves like a convex lens.

[0048] The resulting material is a ceramic-like structure, preferably a film, with sufficient organic functionality to produce an active surface structure. During the conversion to a glass-like ceramic structure, metals are introduced into the structure and, in the case of organofunctional silanes, organic groups are also introduced, provided that the organofunctional groups are stable under the conversion conditions. Organofunctional SiO2 films are readily formed at temperatures below about 300°C. Thus, the addition of at least one organofunctional alkoxysilane to a silsesquioxane-based polymer can introduce organic functional groups during dispensing / writing to vary the concentration and produce a gradient.

[0049] For example, a SiO2-rich structure can be formed from two organofunctional silanes with different hydrophobic / hydrophilic properties, such as one hydrophobic silane and one hydrophilic silane. During deposition of the SiO2-rich film, the relative ratio of the hydrophilic and hydrophobic ratios can be varied such that the coating composition initially contains a larger percentage of a hydrophilic silane and a smaller percentage (or no) hydrophobic silane in addition to the silsesquioxane, with the relative amounts of the two silanes changing during deposition so that they are equal in the middle of deposition and then reversed at the end. That is, at the end of deposition, there is a larger percentage of a hydrophobic silane and a smaller percentage (or no) hydrophilic silane. The resulting material will exhibit a gradient hydrophilic / hydrophobic property: one end is more hydrophilic and the other end is more hydrophobic. This varying hydrophilic / hydrophobic property can be observed by applying a water droplet to the SiO2-rich structure and observing the difference in wettability and diffusion from one end to the other, or by measuring the contact angles at both ends. Exemplary syntheses such as Figure 1 shown.

[0050] When only one alkoxysilane (or metal alkoxide, as described below) is used, varying the relative concentration of that component in the coating composition will result in gradient properties from one end of the structure or film to the other. Gradient properties are not limited to hydrophilicity / hydrophilicity, but can also include, but are not limited to, refractive index and covalent reactivity.

[0051] The method described herein can also be used as a convenient method to incorporate different metal oxides such as germanium oxide, tantalum oxide, titanium oxide, zirconium oxide and hafnium oxide into SiO2-rich structures, where the metal oxide concentration is varied. This conversion process provides a method to build thin SiO2 structures on various substrates through bottom-up manufacturing. Structures incorporating oxides of these other elements (such as germanium, titanium, zirconium, hafnium and tantalum) can form gradient refractive index (GRIN) structures. Due to the lack of organic content in these materials, they can be processed at higher temperatures.

[0052] The SiO2-rich materials described herein can be applied by spin coating deposition, microcontact printing, 3-D printing, or direct writing using methods known in the art, or can be developed to produce films with uniform / homogeneous properties if desired, and to achieve densities exceeding 80% of thermally grown oxides. In the case of direct writing, films with gradient functionality can be achieved by continuously adjusting the relative flow rates of the components. Variable functionality can include hydrophobic-hydrophilic balance, refractive index, and / or covalent reactivity. The resulting material is a ceramic-like composition that is produced as a thermally stable physical element.

[0053] While not wishing to be bound by theory, the apparent incorporation mechanism is primarily an acid-induced hydrolysis-condensation pathway available after the elimination phase of the ceramic conversion reaction. The presence of silanols in the silsesquioxane appears to be beneficial. High concentrations of silanol (hydroxyl) groups are desirable because they promote reaction with alkoxysilanes.

[0054] During the deposition process, when the alkoxysilane or metal alkoxide is distributed into the reaction mixture, an intermediate composition is formed. In a specific example of a material produced from 2-acetoxyethyl silsesquioxane, isobutyl triethoxysilane and methoxy (polyethyleneoxy) propyl trimethoxy silane, the intermediate is a mixture of (acetoxyethyl silsesquioxane) - (acetoxyethyl-isobutyldimethoxysiloxy) siloxane copolymer, acetoxyethyl silsesquioxane and isobutyl trimethoxy silane.

[0055] For the preferred solution coating method, the solution is generally formed by simply dissolving or suspending the silsesquioxane polymer in a solvent or solvent mixture. The solvent that can be used in this method is preferably a volatile medium polar solvent, which can include an organic solvent selected from the group consisting of aromatic hydrocarbons and epoxy functional derivatives thereof, glycol ethers, alkanes and epoxy functional derivatives thereof, ketones, esters such as monomethyl ether acetate, orthoesters, chlorinated hydrocarbons, chlorofluorocarbons, and alcohols. Exemplary organic solvents include diethylene glycol dimethyl ether (diethylene glycol dimethyl ether), dimethoxyethane, methoxyethyl acetate, toluene, and alcohols such as ethanol, methoxypropanol, propoxypropanol, and propylene glycol. Particularly preferred solvents include diethylene glycol dimethyl ether and methoxypropanol.

[0056] Halogen-absorbing solvents are particularly useful as coating solvents and include orthoesters (e.g., trimethyl orthoformate) and epoxy-functional solvents (e.g., butylene oxide). These solvents are believed to be useful because they have the ability to react with the byproduct hydrogen chloride or with intermediate Si--Cl-containing species, thereby slowing the reaction rate and eliminating corrosive byproducts.

[0057] A coating composition is applied to the substrate, which is a liquid containing a silsesquioxane-based polymer having varying concentrations of an alkoxysilane or metal alkoxide forming the reaction product of various compositions, optionally in an organic solvent. Coating methods such as spin coating, spray coating, dip coating or flow coating can be used. For application to a circular substrate, for example, the coating composition can be applied by conventional spin-on-glass (SOG) techniques to form a gradient between the periphery and the center of the substrate.

[0058] After the coating composition is applied to the substrate, the coating solvent is evaporated by simple air drying, by exposure to ambient air, or by application of vacuum or mild heat.

[0059] Although the above methods focus primarily on using solution protocols, those skilled in the art will recognize, in light of the present disclosure, that other equivalent coating means (eg, melt coating) will also work herein and are contemplated to be within the scope of the present disclosure.

[0060] The formation of a structure (e.g., film) rich in SiO2 is achieved by treating the coated substrate at a moderately elevated temperature or by UV irradiation to convert the silsesquioxane deposition polymer composition into a ceramic film rich in SiO2. The crosslinking conversion is carried out in a water-containing atmosphere containing at least about 0.5% relative humidity, preferably containing about 15% relative humidity to about 100% relative humidity. During the entire processing process of forming the ceramic film, a specific level of moisture can be present in the atmosphere, or, alternatively, can only be present during a portion of the process. It should be noted that the high content of silanol groups (Si--OH) that are usually present in the silsesquioxane of the base polymer or deposition polymer also seems to contribute to the crosslinking reaction that occurs during the conversion process, and can reduce the relative humidity level required for the effective conversion of the silsesquioxane polymer into a ceramic film rich in SiO2. A method of inducing silanol formation is to utilize a silsesquioxane copolymer in which a hydrolyzable group is present, such as an acetoxyethyl silsesquioxane-methoxypropoxy silsesquioxane copolymer, and expose them to a high humidity environment during the deposition process and before thermal or UV ceramicization.

[0061] In addition, in the atmosphere containing moisture, other components are not important, and inert gases such as nitrogen, argon, and helium may exist, and reactive gases such as air, oxygen, hydrogen chloride, and ammonia may also exist.

[0062] In one embodiment of the present invention, the conversion of the silsesquioxane deposited polymer on the coated substrate is achieved by a heat treatment of heating the coated substrate. For chloroethyl silsesquioxane or fluoride catalyzed tetrabutylammonium fluoride, acetoxyethyl silsesquioxane resins, the temperature used in the heating process is moderate, preferably at least about 100°C, more preferably at least about 150°C. Extremely high temperatures are unnecessary and are generally detrimental to other materials present on the substrate (e.g., particularly metallized electronic substrates). Heating temperatures in the range of about 150°C to about 700°C are preferred, and for uncatalyzed silsesquioxane polymers, temperatures in the range of about 250°C to about 500°C are more preferred.

[0063] The exact temperature will depend on factors such as the specific β-substituted organosiliconesquioxane polymer used, the atmosphere composition (including relative humidity), the heating time, the coating thickness, and the coating composition components (e.g., fluoride catalysts), all of which may affect the conversion temperature. For example, it has been found that the presence of fluoride can significantly reduce the resin conversion temperature, and halide-substituted resins convert at lower temperatures than resins containing acetoxy groups. In some cases, it may be necessary to remove any solvent present at temperatures below ceramicization to reduce stress cracking. For example, evaporation of the solvent by maintaining the temperature between 50°C and 120°C prior to ceramicization reduces the outgassing burst that may occur if the dissolved deposited polymer is rapidly heated to the ceramic conversion temperature, which may have a negative impact on the ability to form a film.

[0064] The heating time is usually sufficient to form the desired SiO2-rich ceramic film. The heating time is usually in the range of up to about 6 hours. Preferably, it is less than about 2 hours, such as a heating time of about 0.1 to about 2 hours.

[0065] The heating process is usually carried out at ambient pressure (i.e., atmospheric pressure), but pressures below atmospheric pressure or partial vacuum or superatmospheric pressure can also be used. Any heating method, such as using a convection oven, rapid thermal processing, a hot plate or radiant energy or microwave energy, is generally effective. In addition, the heating rate is not critical, but it is most practical and preferred to heat as quickly as possible.

[0066] In an alternative embodiment of the present invention, the formation of the SiO2-rich structure is achieved by subjecting the coated substrate to ultraviolet (UV) irradiation. It has been found that exposing the coated substrate to UV wavelength light can affect the cross-linking transformation of the desired silsesquioxane polymer in the coated substrate. The UV irradiation treatment is typically performed without subjecting the coated substrate to the elevated temperatures used in thermal processing, but a combination of UV irradiation and thermal processing treatments may be employed if desired.

[0067] SiO2-rich structures formed using UV light treatment are generally characterized by having a higher SiO2 content than those produced by conventional thermal treatment under otherwise identical coating conditions. The advantage of using UV treatment is that patterned films can be produced on the substrate by selectively focusing UV irradiation.

[0068] The invention will now be described with reference to the following non-limiting examples.

[0069] Example 1

[0070] Writing a gradient transparent glass-like ceramic structure is accomplished by using three syringe pumps connected and feeding a mixing chamber adjacent to the dispensing hole at the end of the tip. The mixture is dispensed onto a glass slide fixed on a moving bed to provide a continuous film. As described in U.S. Patent No. 6,770,726, the central larger syringe pump provides a continuous flow of a freshly prepared 20% solution of 2-acetoxyethyl silsesquioxane polymer in methoxypropanol. The two peripheral pumps contain isobutyltriethoxysilane and methoxy(polyethyleneoxy)propyltrimethoxysilane, respectively. The amount of silane added is independently varied between 5.5v% and 0% of the silsesquioxane polymer at the midpoint. That is, the concentration of the hydrophobic silane is reduced from 5.5v% at the beginning of deposition to 0v% at the midpoint, and the concentration of the hydrophilic silane is increased from 0v% at the midpoint to 5.5v% at the end of deposition. Therefore, different compositions of silsesquioxane deposited polymers are produced during the mixing process. After removing the solvent by heating at 110°C for 4 hours in air, a transparent film remains. Upon further heating to ~250°C at ~60% relative humidity (RH), the film becomes translucent. The TGA weight loss of the solvent-free film in air at a temperature of 500°C is 47%. The control TGA of the base silsesquioxane is 44%. This comparison is very consistent with the incorporation of organic functional groups into glassy ceramics. One end is hydrophobic with a static water contact angle of 85° and the other end is relatively hydrophilic with a static water contact angle of 15°. When octadecyltrimethoxysilane is replaced with isobutyltriethoxysilane under the same conditions, the static water contact angle is 100° at the hydrophobic end.

[0071]

[0072] Example 2 (prediction)

[0073] The base polymer of Example 1 was treated as a 20% methoxypropanol solution and aged for about two weeks. It was observed that the acetoxy groups migrated from 2-ethyl silicon to the silicon backbone and were then replaced by methoxypropanol to form acetoxyethylsilsesquioxane-methoxypropoxysilsesquioxane copolymers. The ratio of 2-ethylacetoxy to methoxypropyl groups was 6:1, and the density of the resulting thin film ceramic material was 1.55 g / mL. Gradient deposition was performed under the same conditions as Example 1.

[0074] Example 3 (prediction)

[0075] The method described in Example 1 was repeated under the same conditions using germanium isopropoxide as a replacement for the two silanes, increasing the refractive index.

[0076] Example 4 (Prediction)

[0077] The method described in Example 1 was repeated under the same conditions using dimethyldimethoxysilane as a replacement for one or both of the silanes, resulting in a decrease in the modulus of the coating.

[0078] Those skilled in the art will appreciate that the above-described embodiments may be modified without departing from the broad inventive concept thereof. In addition, based on the present invention, those of ordinary skill in the art will further recognize that the relative proportions of the above-described components may be changed without departing from the spirit and scope of the present invention. Therefore, it should be understood that the present invention is not limited to the specific embodiments disclosed, but is intended to cover modifications within the spirit and scope of the present invention as defined by the appended claims.

Claims

1. A SiO2-rich structure having gradient properties, wherein the structure is formed from a silsesquioxane having electronegative β-substituents and at least one organofunctional silane, wherein: SiO2-rich means that a plurality of silicon atoms are each bonded to four oxygen atoms, and no more than 50% of the silicon atoms are bonded to carbon atoms.

2. The SiO2-rich structure of claim 1, wherein the structure has a gradient hydrophobicity / hydrophilicity: one end is more hydrophilic and the other end is more hydrophobic.

3. The SiO2-rich structure of claim 1, wherein the silsesquioxane has a halogen, ether or carboxylate functional group at the β position.

4. The SiO2-rich structure of claim 3, wherein the silsesquioxane is 2-acetoxyethyl silsesquioxane.

5. The SiO2-rich structure of claim 1, wherein the at least one organofunctional silane is a dialkyldialkoxysilane or an alkyltrialkoxysilane.

6. The SiO2-rich structure of claim 5, wherein the at least one organofunctional silane is a dialkyldimethoxysilane or a dialkyldiethoxysilane.

7. The SiO2-rich structure of claim 5, wherein the at least one organofunctional silane is an alkyltrimethoxysilane or an alkyltriethoxysilane.

8. The SiO2-rich structure of claim 1, wherein the at least one organofunctional silane is methoxy(polyethyleneoxy)propyltrimethoxysilane or isobutyltriethoxysilane.

9. The SiO2-rich structure of claim 1, wherein the structure is formed from 2-acetoxyethylsilsesquioxane, methoxy(polyethyleneoxy)propyltrimethoxysilane, and isobutyltriethoxysilane.

10. The SiO2-rich structure of claim 1, wherein a plurality of silicon atoms are each bonded to four oxygen atoms, and no more than 50% of the silicon atoms are bonded to carbon atoms.

11. The SiO2-rich structure according to claim 1, characterized in that The structure is a ceramic membrane.

12. The SiO2-rich structure of claim 11, wherein the ceramic film has a thickness of 15 to 500 nanometers.

13. A SiO2-rich structure having a gradient concentration of at least one metal oxide selected from the group consisting of oxides of germanium, tantalum, titanium, zirconium and hafnium, wherein the structure is formed from a corresponding metal alkoxide and a silsesquioxane having an electronegative β-substituent, wherein: SiO2-rich means that a plurality of silicon atoms are each bonded to four oxygen atoms, and no more than 50% of the silicon atoms are bonded to carbon atoms.

14. The SiO2 rich structure of claim 13, wherein the SiO2 rich structure has a gradient refractive index.

15. A method for forming a SiO2-rich structure having gradient properties, the method comprising preparing a coating composition comprising a silsesquioxane having electronegative β-substituents, at least one organofunctional silane, and optionally a solvent, applying the mixture to a substrate, and heating and / or UV irradiating the coated substrate, wherein: SiO2-rich means that a plurality of silicon atoms are each bonded to four oxygen atoms, and no more than 50% of the silicon atoms are bonded to carbon atoms.

16. The method of claim 15, wherein the coating composition comprises a volatile polar solvent.

17. The method of claim 15, wherein the coating comprises spin coating deposition, 3D printing, microcontact printing, or direct writing.

18. The method of claim 15, wherein the heating and / or UV irradiation is performed in an atmosphere containing at least 0.5% relative humidity.

19. The method of claim 15, wherein the heating is performed at 150°C to 700°C.

20. The method of claim 15, wherein the step of coating comprises adjusting relative flow rates of the at least one organofunctional silane.

21. The method of claim 15, wherein during the coating step, the concentration of at least one organofunctional silane in the coating composition is varied to produce a SiO2-rich structure having a gradient nature.

22. A method for forming a SiO2-rich structure having gradient properties, the method comprising preparing a coating composition comprising a silsesquioxane having electronegative β-substituents, at least one metal alkoxide, and optionally a solvent, applying the mixture to a substrate, and heating and / or UV irradiating the coated substrate, wherein: SiO2-rich means that a plurality of silicon atoms are each bonded to four oxygen atoms, and no more than 50% of the silicon atoms are bonded to carbon atoms.

23. The method of claim 22, wherein the metal alkoxide is selected from the group consisting of germanium isopropoxide, tantalum ethoxide, titanium n-butoxide, zirconium n-propoxide, and hafnium n-butoxide.

24. The method of claim 22, wherein the SiO2-rich structure has a gradient refractive index.

25. The method of claim 22, wherein the SiO2-rich structure has a gradient metal oxide concentration.

26. The method of claim 22, wherein the coating step comprises adjusting relative flow rates of the at least one metal alkoxide.

27. The method of claim 22, wherein during the coating step, the concentration of at least one metal alkoxide in the coating composition is varied to produce a SiO2-rich structure having a gradient nature.

Citation Information

Patent Citations

  • Coatings for microelectronic devices and substrates

    US5290354A

  • Transparent oil-in-water microemulsion flavor concentrate

    US5320863A

  • Method of using siloxane polymers

    US5853808A

  • beta-substituted organosilsesquioxane polymers

    US6770726B1

  • Gas barrier layer of plastic film for the use of display

    KR1020030082814A